Paxillin and embryonic PolyAdenylation Binding Protein (ePABP) engage to regulate androgen-dependent Xenopus laevis oocyte maturation - A model of kinase-dependent regulation of protein expression. (15th June 2017) - Miedlich, Susanne U.; Taya, Manisha; Young, Melissa Rasar; Hammes, Stephen R.
Abstract: Steroid-triggered Xenopus laevis oocyte maturation is an elegant physiologic model of nongenomic steroid signaling, as it proceeds completely independent of transcription. We previously demonstrated that androgens are the main physiologic stimulator of oocyte maturation in Xenopus oocytes, and that the adaptor protein paxillin plays a crucial role in mediating this process through a positive feedback loop in which paxillin first enhances Mos protein translation, ensued by Erk2 activation and Erk-dependent phosphorylation of paxillin on serine residues. Phosphoserine-paxillin then further augments Mos protein translation and downstream Erk2 activation, resulting in meiotic progression. We hypothesized that paxillin enhances Mos translation by interacting with embryonic PolyAdenylation Binding Protein (ePABP) on polyadenylated Mos mRNA. Knockdown of ePABP phenocopied paxillin knockdown, with reduced Mos protein expression, Erk2 and Cdk1 activation, as well as oocyte maturation. In both Xenopus oocytes and mammalian cells (HEK-293), paxillin and ePABP constitutively interacted. Testosterone ( Xenopus ) or EGF (HEK-293) augmented ePABP-paxillin binding, as well as ePABP binding to Mos mRNA ( Xenopus), in an Erk-dependent fashion. Thus, ePABP and paxillin work together in an Erk-dependent fashion to enhance Mos protein translation and promote oocyte maturation. Highlights: Knockdown of ePABP phenocopies paxillin knockdown in Xenopus laevis oocytes. ePABP is necessary for testosterone-induced oocyte maturation. ePABP knockdown reduces testosterone-induced Mos expression, Erk2 and Cdk1 activation. ePABP and paxillin dynamically interact in response to testosterone (oocytes) or EGF (HEK293). Dynamic ePABP and paxillin interaction depends on Erk-dependent paxillin phosphorylation.